STRATEGI PENGEMBANGAN TANAMAN KEDELAI UNTUK PEMBERDAYAAN EKONOMI RAKYAT DI KABUPATEN KEEROM PROVINSI PAPUA - Rante, Yohanis (Jurnal Manajemen dan Kewirausahaan, 2013)
This study aimed to analyze the internal and external factors that influenced the soybean development strategy in Keerom Regency (Papua). soybean-farmers and stakeholders in 20 less-developed villages, and secondary data on period of 1997−2010 were the sample. The results revealed that the soybeans local-farming had a great financial prospect. The high productivity and its return to the farmers had allowed some proposed development strategies to improve the local soybean production and its product processing indus-tries. The unfair agricultural trading system, cheaper imported soybean, and unstable fertilizer prices were some of the threats that must be addressed.